Pooh goes visiting - Milne, A. A.; Krensky, Stephen Shepard, Ernest H. (Methuen London, 2002)
In "Pooh Goes Visiting," Winnie the Pooh sets off to visit his friend Piglet, hoping to share some honey and enjoy a cozy afternoon together. Along the way, Pooh's gentle antics and heartfelt friendship highlight the joys of companionship and the simple pleasures of life.